1988
DOI: 10.1007/bf01132183
|View full text |Cite
|
Sign up to set email alerts
|

Duration of storage of cyropreserved human embryos

Abstract: The incidence of cell injury, embryo survival, and implantation following cryopreservation of zygotes and two- to five-cell embryos was studied in 100 patients in order to evaluate the effect of duration of storage. The incidence of individual cell survival was 58% regardless of the length of time kept in liquid nitrogen or the stage of the embryo at freezing. There were 104 of 208 (50%) thawed embryos that survived completely intact, and of those, 24 implanted successfully. Twenty-one (21%) patients had a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…It is difficult to evaluate the significance of this potential effect because limited clinical outcomes were provided. In contrast, Cohen et al (9) found no significant influence of storage time on blastomere survival or clinical pregnancy, but they did not provide live birth data. These investigators found no difference in blastomere survival or pregnancy outcome in cryopreserved embryos stored from 8 to 70 weeks.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is difficult to evaluate the significance of this potential effect because limited clinical outcomes were provided. In contrast, Cohen et al (9) found no significant influence of storage time on blastomere survival or clinical pregnancy, but they did not provide live birth data. These investigators found no difference in blastomere survival or pregnancy outcome in cryopreserved embryos stored from 8 to 70 weeks.…”
Section: Discussionmentioning
confidence: 87%
“…However, pregnancy outcomes in that study may have been confounded because the transfers occurred during natural and clomiphene citrate cycles. In both reports, embryos were frozen for a relatively short period (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it appears that the duration of cryo-storage will not affect the outcome of frozen embryos. Several studies carried out in humans indicated that long-term cryo-storage did not affect embryo cryo-survival and pregnancy outcome in the IVF or embryo donation program [31,32]. However, a previous study reported that increased rates in embryonic cell death were found associated with cryo-storage of indicates that the embryos developed to 8-cell stage in the group of cryo-storage for 90-92 days was significantly reduced compared with the group of cryostorage for 8-10 days and the control group, which were similar indicated by a .…”
Section: Discussionmentioning
confidence: 99%
“…An early report by Testart et al (5) found an increase in the rate of embryonic cell death after only a few months of cryostorage. However, Cohen et al (6) showed that the increased length of cryostorage does not have an effect on embryo development and potential. Our center recently reported on a large number of frozen-thawed embryos (more than 11,000) and concluded that the length of storage did not effect survival, implantation, miscarriage, or live birth rates with pronuclear and cleavage stage frozen embryos (4).…”
mentioning
confidence: 98%